Polish regulatory system regarding ATMP hospital exemptions - Pachocki, Jan; Verter, Frances (Frontiers in Immunology, 2024)
This article explains the current regulatory system in Poland regarding Advanced Therapy Medicinal Products given under Hospital Exemptions (ATMP-HE). The relevant sections of Polish legislation are translated into English and their interaction is described. We analyze the impact of these regulations from the perspective of three stakeholder groups: manufacturers, physicians, and patients. Amendments enacted between 2018 and 2023 have substantially changed Polish implementation of the ATMP-HE pathway. In Poland, most ATMP-HE treatments have been therapies employing Mesenchymal Stromal Cells (MSC). Comparison to other European countries shows that Poland is within the mainstream of EU practices regarding ATMP-HE implementation. One notable issue is that Poland has relatively low per capita spending on healthcare, and ATMP-HE in Poland must be funded from outside the government healthcare system.